QGIS approach to extract fluvial terraces for archaeological purposes using remote sensing data - Duarte, Lia (2018)
Fluvial terraces, normally defining flattened surfaces are significant geomorphic features that explains the presence of rivers at high altitudes and constitute the remains of the old river along the valley. In Iberia, many of these terraces preserve Paleolithic artifacts and document the presence of the first human communities. Nowadays, the increasing use of Free and Open Source Software (FOSS) provides the opportunity to analyze and test different approaches to study these geomorphological features. According to the literature, several algorithms from open source GIS software have been used, such as Geographic Resources Analysis Support System (GRASS) GIS. In the recent versions, QGIS, a GIS open source software, is integrated with several algorithms from other software, such as GRASS GIS, System for Automated Geoscientific Analyses (SAGA), Orfeo-ToolBox (OTB), among others. Therefore, the procedures used to extract and identify fluvial terraces can be performed using QGIS software. The objective of this work was to combine Remote Sensing data and GIS algorithms in QGIS to identify fluvial terraces in order to support archaeological prospection of Paleolithic artifacts along the Minho River (Portugal border). Different data were used such as Digital Surface Model (DSM), slope derived from DSM, Normalized Difference Vegetation Index (NDVI) map derived from Sentinel 2A images (summer), Land Use Land Cover (LULC) derived from Corine Land Cover (CLC) and hydrological data from Minho valley. The method proposed allowed the definition of a fluvial staircase considering several terraces levels along the Minho valley. The data used were in WGS84 UTM zone 29 (EPSG:32629) and the spatial resolution adopted was 10 meters. Different scenarios were tested and the results were validated considering in situ measurements, in order to find the best weight associated to each parameter.